Особливості визначення податкового навантаження на рівні держави та регіону - Цимбалюк, Ірина Олександрівна; Tsymbaliuk, Iryna O.; Міщанчук, Ольга Олександрівна; Mishchanchuk, Olha O. (Хмельницький національний університет, 2014)
Досліджено сутність й особливості визначення податкового навантаження. Оцінено рівень податкового навантаження у Волинській області. Виявлено та обґрунтовано проблеми та перспективи оптимізації податкового навантаження в Україні.

The purpose of the article is to explore the nature of approaches and methods for calculating the tax burden and the study of the tax burden on the state and its regions (for example, Volyn region).The article discussed different approaches to the definition of "tax burden." It was found that the tax burden - a generalized parameter which characterizes the value of tax exemptions for micro, meso level and at the macro level. However, to date, practically there aren't any researches of the tax burden at the meso level. The analysis of the tax burden of Volyn region based on the methodology proposed by V. Grigorenko showed, that coefficient, calculated as the ratio of tax revenues to the region GRP reflects the fiscal independence of the territory, but not the level of the tax burden. For an objective determination of the tax burden on the regional level suggest to consider the whole volume payments made by the respective territory to all budgets, including those which was provided to state budget and state social insurance funds. The situation of concerning the tax burden may reflect the partial indices that are calculated as the ratio between the amount of individual income taxes and fees and tax bases of these payments. Calculation of the tax burden at the region is difficult due to lack of information on the revenue of all budget and state funds in individual regions.
Specifics of determining the tax burden on the state and region
Keywords: податки; податкове навантаження; оптимальний рівень податкового навантаження; податкові надходження; tax burden; levels of the tax burden; optimal level of the tax burden